Synthesis and Characterization of Polyurethane– Organoclay Nanocomposites Based on Renewable Castor Oil Polyols - M. A., Alaa; Kamal, Yusoh; S. F., Hasany (Springer Berlin Heidelberg, 2014)
In this study, castor oil-based polyurethanes–organoclay (COPUs-Cloisite 30B) nanocomposites are synthesized by mixing polypropylene glycol polyol and dehydrated castor oil (15 %), enforced with C30B nanofillers, at different weight percentages. The physico-chemical behaviors were evaluated by Fourier transform infrared spectroscopy, Fourier scanning electron microscopy, scanning electron microscopy and X-ray diffraction. Thermal stability was found improved up to ~30 °C in the sample with 5 wt% of C30B. Tensile properties depicted an improvement of ~240 % in tensile strength and decrease of ~30 % in elongation with 5 wt% organoclay, respectively. Improved physico-chemical properties of COPUs-C30B signify the usage of COPUs-C30B in the industrial and commercial applications, i.e. coatings, adhesives and automotive applications.